Assessing the Affordances of SimReal+ and their Applicability to Support the Learning of Mathematics in Teacher Education - Hadjerrouit, Said (Issues in informing science & information technology education, 2017)
Aim/Purpose: Assess the affordances and constraints of SimReal+ in teacher education Background There is a huge interest in visualizations in mathematics education, but there is little empirical support for their use in educational settings Methodology: Single case study with 22 participants from one class in teacher education. Quantitative and qualitative methods to collect students’ responses to a survey questionnaire and open-ended questions Contribution: The paper contributes to the understanding of affordances and constraints of visualization tools in mathematics education Findings: The visualization tool SimReal+ has potential for learning mathematics in teacher education, but the user interface should be improved to make it more usable for different users. Teachers need to consider technological and pedagogical affordances of SimReal+ at the student, classroom, and mathematics subject level Recommendations for Practitioners: Address technological and pedagogical affordances of SimReal+ Recommendation for Researchers: Improve the design of SimReal+ to make it technologically and pedagogically more usable Impact on Society: Understand the affordances and constraints of visualization tools in education Future Research: Implement a next cycle of experimentation with SimReal+ in teacher education to ensure more validity and reliability